1991
DOI: 10.1148/radiology.181.3.1947077
|View full text |Cite
|
Sign up to set email alerts
|

Fast selective black blood MR imaging.

Abstract: To overcome the problems associated with gradient-echo (GRE) magnetic resonance (MR) angiography ("bright blood" imaging) and "black blood" imaging with presaturated spin-echo (SE) pulse sequences, the authors devised a new approach for black blood imaging. Their method, selective preinversion fast imaging with steady precession (turboFISP), uses a segmented GRE sequence for fast data acquisition. Nulling of vascular signal results, and stationary tissue appears bright. The method was compared with flow-compen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
232
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(234 citation statements)
references
References 11 publications
0
232
0
2
Order By: Relevance
“…Here, in one of the first studies to assess the measurement capabilities of MRI in the carotid artery at 3T, we demonstrated the high reproducibility of vessel wall area measurements using a dual-inversion segmented k-space GRE imaging technique. Table 4 Means, SDs, Intra-and Interobserver MAD and MRE for all Endpoints Black-blood techniques are commonly used to achieve flow suppression, even though they require a relatively long acquisition duration (32). The technique uses a nonselective inversion RF pulse that inverts the longitudinal magnetization of the entire volume in the transmit coil.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in one of the first studies to assess the measurement capabilities of MRI in the carotid artery at 3T, we demonstrated the high reproducibility of vessel wall area measurements using a dual-inversion segmented k-space GRE imaging technique. Table 4 Means, SDs, Intra-and Interobserver MAD and MRE for all Endpoints Black-blood techniques are commonly used to achieve flow suppression, even though they require a relatively long acquisition duration (32). The technique uses a nonselective inversion RF pulse that inverts the longitudinal magnetization of the entire volume in the transmit coil.…”
Section: Discussionmentioning
confidence: 99%
“…2a. A turbo spin-echo pulse sequence (turbo factor 17) preceded by a double-inversion preparation phase [6] was used. The field of view was 18 cm x 18 cm with a matrix size of 256 x 256, yielding an in-plane resolution of 0.70 mm x 0.70 mm pixel size.…”
Section: Methodsmentioning
confidence: 99%
“…Black-blood imaging methods (9)(10)(11)(12)(13)(14), wherein blood signals are selectively suppressed using spatial presaturation (9,10), double inversion recovery (11,12), or motion-sensitizing magnetization preparation (13,14), if successfully combined with CE 3D MP-RAGE, may have the potential to provide an excellent differentiation between blood and tumors. However, it is challenging to achieve CE black-blood imaging due to a rapid recovery of blood signals along the echo train in MP-RAGE.…”
mentioning
confidence: 99%